A comparative study of the economic profitability of the xero graphic copying businesses in the downtown area, Iloilo City, Jan. 1985-Jan. 1989. - Mercado, Jivette T
This comparative study deals with the economic profitability of the different types of copying business namely: single and chain and the different types of machines used by each type of copying business: a) single copying centers using simple machines; b) single copying centers using both simple and complex machines; c) chain copying centers using simple machines; and d) chain copying using both simple and complex machines., The cost structure and economic profitability of the Xerographic copying business in the Downtown area City from January, 1988 to January 1989 was considered. Data were gathered from owners and managers of 43 copying centers located in Iznart, J. M. Basa, Rizal, Ortiz, Aduana, Arcenal, Aldeguer, Arroyo, Guanco, Solis, Yulo and Mapa streets. This study was conducted from the last week of November, 1989 to the last week of December, 1989. The respondents were interviewed with the use of an interview schedule. Results showed that, on the average, chain copying centers were more economically profitable than single copying centers and that those operating in chain using both simple and complex machines yield higher economic profit than those using only simple machines.